Developing a Patient Classification System for a Neonatal ICU. (December 2016) - Daraiseh, Nancy M.; Vidonish, William P.; Kiessling, Pam; Lin, Li
Abstract : OBJECTIVE: The purpose of this study was to develop a valid and reliable patient classification system (PCS) for a neonatal ICU (NICU). BACKGROUND: PCSs have been widely used to determine required care hours, budgeting, and staffing. There is a lack of and a vital need for a valid and reliable pediatric PCS because of differences in needs and treatment from adults. METHODS: Data were collected in a NICU using work sampling, chart reviews, and expert opinion. The resulting PCS was assessed for validity and reliability, ease of use, effectiveness, and satisfaction. RESULTS: The PCS showed significantly high reliability and validity. Survey scores revealed nurses perceived the tool to be easy to use and effective. CONCLUSIONS: Using subjective and objective methods, a NICU PCS was shown to be a valid and reliable measure to determine the hours per patient day required to provide care.